Pelatihan Kewirausahaan bagi Santri Pondok Pesantren Tahsinul Khuluq - Redaputri, Appin Purisky; Barusman, Tina Miniawati; Waskito, Budhi; Sugito, Sugito; aminah, aminah; Hartabela, Dadang (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2025)
The goal of this entrepreneurship training program is to develop entrepreneurial skills that are relevant to Islamic values and prepare students to face the challenges of the business world. The methods used include curriculum development that integrates entrepreneurship education into existing subjects, with an emphasis on practical application through real-life projects such as managing small businesses and cooperatives. Entrepreneurial skills are assessed through business project evaluations and presentations, as well as reflective practice that allows students to articulate their learning experiences. The results of this program indicate that ongoing feedback from students and mentors is essential to improving the effectiveness of future training. In conclusion, this training not only equips students with practical skills, but also inspires them to pursue entrepreneurial endeavors that are in line with the values they hold.